2014
DOI: 10.3748/wjg.v20.i37.13453
|View full text |Cite
|
Sign up to set email alerts
|

Interventional treatment for unresectable hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the sixth most common cancer and third leading cause of cancer-related death in the world. The Barcelona clinic liver cancer classification is the current standard classification system for the clinical management of patients with HCC and suggests that patients with intermediate-stage HCC benefit from transcatheter arterial chemoembolization (TACE). Interventional treatments such as TACE, balloon-occluded TACE, drug-eluting bead embolization, radioembolization, and combined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 102 publications
0
31
0
Order By: Relevance
“…Therapy for HCC is still inefficacious. The tyrosine kinase inhibitor, Sorafenib, despite its limitations, such as low overall response rates and high toxicity, was the first systemic targeted therapy approved by the US Food and Drug Administration for the treatment of advanced HCC [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapy for HCC is still inefficacious. The tyrosine kinase inhibitor, Sorafenib, despite its limitations, such as low overall response rates and high toxicity, was the first systemic targeted therapy approved by the US Food and Drug Administration for the treatment of advanced HCC [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modified TACE procedures, such as superselective TACE, selective balloon-occluded TACE, and TACE under balloon occlusion of the hepatic vein or the corresponding portal vein branch, have been developed to obtain a complete necrosis of the tumor [121]. Alternative strategies, including the combination of systemic therapy with TACE, have also been investigated to improve TACE-based regimens.…”
Section: Transarterial Therapymentioning
confidence: 99%
“…For example, incomplete HCC treatment via TACE can result in increased levels of angiogenic factors, leading to tumor growth and metastasis. 139 A novel study conducted by the MD Anderson Cancer Center Group demonstrated that machine learning may play a role in predicting patient response to TACE using quantitative imaging features in combination with the BCLC staging system. 140 Other machine learning applications in interventional oncology include intraprocedural support, such as catheter guidance, and postprocedural assessment, such as posttreatment MRI-based texture analysis of tumors.…”
Section: Future Therapiesmentioning
confidence: 99%